Front Cover. Issue 5 (3rd September 2018) - Cordero, Gerardo A.; Liu, Haibo; Wimalanathan, Kokulapalan; Weber, Rachel; Quinteros, Kevin; Janzen, Fredric J.
Abstract : The cover image, by Gerardo A. Cordero et al., is based on the Research Gene network variation and alternative paths to convergent evolution in turtles, DOI:10.1111/ede.12264 . Photo credit: Gerardo Antonio Cordero.